Investigation of antioxidative constituents from Murraya koenigii leaves (curry leaves) and its antibacterial activity against plant disease-caused microbe / Norfatihah Syaifudin - Syaifudin, Norfatihah (2019)
The study was carried out on the leaves of Murraya koenigii which belongs to Rutaceae family that can be found abundantly all around asia especially India. This genus of species comprises variety of medicinal value. The objective of this study is to isolate the antioxidative constituents of M.koenigii by using phytochemical analysis of methanol extract that indicated the most abundance presence of tannins followed by triterpenoids, flavonoids and Cardiac glycosides. The next phytochemical analysis which used certain spraying on three extracts which are hexane, ethyl acetate (EA) and methanol was also done in order to identify the antioxidative compounds existed. The selected isolated compounds are labelled as E4 and H4 from EA and hexane respectively. They are being further analysed by using FTIR and 1H NMR spectroscopy to predict their structures. As for the result, E4 might be an antioxidative aromatic phenolic glycosides and H4 as an antioxidative aromatic terpenoid glycosides. As for the next objective, the effectivesness of the extracts toward plant disease-caused microbes by inhibiting the growth of Erwinia chrysanthemi is also measured and proven through their zones of inhibition. The most effective extract is EA extract since it has the biggest inhibition zone between the three extracts which is at 11.0 mm